2018
DOI: 10.1021/acsami.8b14577
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Near-Infrared Absorbing n-Type Porphyrin Acceptor for Organic Solar Cells

Abstract: While the outstanding charge transport and sunlightharvesting properties of porphyrin molecules are highly attractive as active materials for organic photovoltaic (OPV) devices, the development of ntype porphyrin-based electron acceptors has been challenging. In this work, we developed a high-performance porphyrin-based electron acceptor for OPVs by substitution of four naphthalene diimide (NDI) units at the perimeter of a Zn-porphyrin (P Zn ) core using ethyne linkage. Effective πconjugation between four NDI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Furthermore, they found that the introduction of alkyl chains on porphyrin enhanced the aggregation of these porphyrin‐based molecules compared with aromatic side groups, which had a significant influence on physicochemical properties such as electrochemical behavior, crystallinity, and nonradiative recombination loss. Hadmojo et al synthesized a porphyrin‐based small molecule, P Zn ‐TNDI, by introducing four naphthalene diimide (NDI) units to the perimeter of the zinc porphyrin core via ethyne linkages . Benefiting from the effective ICT between porphyrin and NDI, the molecule exhibits a low bandgap of 1.33 eV.…”
Section: Nir Photoelectric Materials For Opvsmentioning
confidence: 99%
“…Furthermore, they found that the introduction of alkyl chains on porphyrin enhanced the aggregation of these porphyrin‐based molecules compared with aromatic side groups, which had a significant influence on physicochemical properties such as electrochemical behavior, crystallinity, and nonradiative recombination loss. Hadmojo et al synthesized a porphyrin‐based small molecule, P Zn ‐TNDI, by introducing four naphthalene diimide (NDI) units to the perimeter of the zinc porphyrin core via ethyne linkages . Benefiting from the effective ICT between porphyrin and NDI, the molecule exhibits a low bandgap of 1.33 eV.…”
Section: Nir Photoelectric Materials For Opvsmentioning
confidence: 99%
“…4 Among such structural modifications, the π-extension of the Por core is particularly appealing, since it leads to compounds with a strong near-infrared (NIR) absorption, stemming from a small highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) gap. 12 Such π-extended Pors can be obtained either by attaching other aromatic units to the macrocycle via conjugative linkers 9,[13][14][15][16] or through the meso,β-fusion of aromatic units via intramolecular oxidative coupling. [17][18][19][20][21][22][23][24] Using the latter synthetic strategy, a wide range of π-extended Pors has been reported, showing, in some cases, absorptions reaching far into the NIR region (i.e., 1417 nm) and optical HOMO- LUMO gaps as low as 0.61 eV.…”
Section: Introductionmentioning
confidence: 99%
“…4 Among such structural modifications, the π-extension of the Por core is particularly appealing, since it leads to compounds with a strong near-infrared (NIR) absorption, stemming from a small highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) gap. 12 Such π-extended Pors can be obtained either by attaching other aromatic units to the macrocycle via conjugative linkers 9,[13][14][15][16] or through the meso,β-fusion of aromatic units via intramolecular oxidative coupling. [17][18][19][20][21][22][23][24] Using the latter synthetic strategy, a wide range of π-extended Pors has been reported, showing, in some cases, absorptions reaching far into the NIR region (i.e., 1417 nm) and optical HOMO- LUMO gaps as low as 0.61 eV.…”
Section: Introductionmentioning
confidence: 99%